Psychological birth order and inferiority feeling as predictors of adult attachment style [Psikolojik doğum sirasi ile yetersizlik duygusunun yetişkin bağlanma stillerini yordama düzeyinin incelenmesi] - SEVİM, ERDEM; EKŞİ, HALİL (Ankara University, 2016)
The aim of this study is to examine predictive power of psychological birth order and inferiority feeling on adult attachment style. In this regard, 191 female volunteers (%72.3) and 73 male volunteers (%27.7), totally 264 students from Marmara University participated in the study. The White-Campbell Psychological Birth Order Inventory, Inferiority Feeling Scale and Experiences in Close Relationships Inventory were used to collect data. In data analysis, Pearson correlation, Independent Sample T test and multiple regression analyses were applied. PBO (Psychological Birth Order) first- born, PBO-Youngest and inferiority feeling scores explain approximately %11 of avoidant attachment sub-dimension within adult attachment styles. PBO-Onlyand and inferiority feeling scores explain approximately %21 of anxious attachment sub-dimension within adult attachment styles. According to the results of the research, it can be said that the individual’s perception relating to the psychological position in his/her family could have a decisive impact on the quality of individual’s adult life relations, as well as the individual’s considerations related to his/her abilities or individual himself/herself together with the patterns developed within the family. © 2016, Ankara University. All rights reserved.
Keywords: Adult attachment style; Inferiority feelings; Psychological birth order